Panicker’s vacuum suction hemostatic device- a novel innovation for the treatment of atonic postpartum hemorrhage - Thomas, Jyothi Susan; Mammen Roy, Mini; Krishnan, Sudha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The aim of this study was to evaluate the effectiveness of the Panicker’s vacuum suction hemostatic device in treating postpartum hemorrhage refractory to medical treatment. Methods: A retrospective study including women with atonic postpartum hemorrhage in whom Panicker’s vacuum suction hemostatic device was used, since they did not respond to the medical management. The demographic factors, mode of delivery, volume of blood loss, blood transfusion and outcome of the procedure were studied. Results: The study demonstrated that the device achieved effective hemostasis in both minor and major PPH, helping reduce maternal morbidity and mortality. Early recognition and timely preventive measures in at-risk women could have limited bleeding and reduced the need for transfusions. Conclusions: Panicker’s vacuum suction hemostatic device which works on the principle of vacuum retraction of the uterus was found to be effective in the management of atonic postpartum hemorrhage.